Comparison of maximum hip abductor torques from patient-specific multibody simulation models with isometric and isokinetic force measurements - Fleischmann, Christopher; Leher, Irina; Scherb, David; Kollerer, Marius; Miehling, Jörg; Wartzack, Sandro; Sesselmann, Stefan (Human Interaction & Emerging Technologies (IHIET 2023): Artificial Intelligence & Future Applications, 2023)
Muscuolskeletal simulations have become an important tool to simulate biomechanical properties. However, adaption of the models to patients or test persons is relevant in order to obtain realistic results (e.g. hip joint moments or muscle forces). It is particularly important to correctly reproduce the patient-specific maximum isometric muscle forces of the individual musculotendinous structures. The purpose of this work is to determine the extent to which gluteal muscle adaptation has an impact on the maximum hip joint moment during hip abduction.Based on MRI images volumes of the gluteal muscles were determined. These were used to calculate the muscles' maximum isometric force via the physiological cross-sectional area and the specific muscle tension. Since the values of the specific tension differ greatly in literature, several models were created. The models were investigated regarding their maximum hip joint moment and compared, first, to a marker-based scaled generic model and, second, to isokinetic and isometric force measurements using a dynamometer.It was shown that both, the models and the muscle strength measurements, show a maximum in the lower area of hip abduction and decrease sharply with increasing abduction. The models with a lower specific tension were much closer to the measured maximum hip torques. Higher values for the specific tension and the model without patient-specific information on the musculature were above the strength measurements. However, all models are clearly above the measurements with increasing abduction.It can be concluded that the gluteal muscles should be simulated with rather lower values of the specific tension.
Keywords: Biomechanics; Isometric Force; Isokinetic force; Muscle segmentation; patient-specific modelling